Question and Answers Forum

All Questions      Topic List

Mensuration Questions

Previous in All Question      Next in All Question      

Previous in Mensuration      Next in Mensuration      

Question Number 216162 by Spillover last updated on 28/Jan/25

Answered by MrGaster last updated on 02/Feb/25

Let x=(π/3)−t⇒dx=−dt  ∫_0 ^(π/3) (√(sin^3 xsin((π/3)−x)))dx∫_(π/3) ^0 (√(sin^3 ((π/3)−t)sin t))(−dt)=∫_0 ^(π/3) (√(sin^3 ((π/3)−t)sin t dt))  ∫_0 ^(π/3) (√(sin^3 x sin((π/3)−x)))dx=∫_0 ^(π/3) (√(sin^3 ((π/3)−x)sin x dx))  ∫_(0 ) ^(π/3) (√(sin^3 x sin((π/3)−x)))dx=(1/2)∫_0 ^(π/2) ((√(sin^3 x sin((π/3)−x)))+(√(sin^3 ((π/3)−x)sin x)))dx  ∫_0 ^(π/3) (√(sin^3 x sin((π/3)−x)))dx=(1/2)∫_0 ^(π/3) (√(sin^3 ((π/3)/2)))dx=(π/(16))  so:  ∫_0 ^(π/3) (√(sin^3 x sin((π/3)−x)))dx=(π/(16))

Letx=π3tdx=dt0π3sin3xsin(π3x)dxπ30sin3(π3t)sint(dt)=0π3sin3(π3t)sintdt0π3sin3xsin(π3x)dx=0π3sin3(π3x)sinxdx0π3sin3xsin(π3x)dx=120π2(sin3xsin(π3x)+sin3(π3x)sinx)dx0π3sin3xsin(π3x)dx=120π3sin3(π3/2)dx=π16so:0π3sin3xsin(π3x)dx=π16

Terms of Service

Privacy Policy

Contact: info@tinkutara.com